The impact of technological innovation on Australia's economic growth and business competitiveness - Abraham, Archie (Privietlab, 2022)
This research explores the impact of technological innovation on economic growth and business competitiveness in Australia. It examines the relationship between technological advancements and productivity, the role of government policies in fostering innovation, and the challenges and opportunities faced by Australian businesses in the digital era. A mixed-methods approach was used, combining quantitative data analysis with qualitative insights, to provide a comprehensive understanding of the subject. The findings highlight the transformative role of technology in driving Australia's economic development while addressing barriers that impede its widespread adoption.